2021
DOI: 10.47709/ijeal.v1i3.1159
|View full text |Cite
|
Sign up to set email alerts
|

The Government Language Style Variation on Covid-19 Post in Instagram

Abstract: This research aim's to investigate language style variation used by the government on a covid-19 post on Instagram. This research is applied the descriptive qualitative method that focused on two objectives of the study. Firstly, to investigate situations types of language style variation were found in social media and secondly, to investigate realized of language style variation in social media in posting Coronavirus disease (covid-19). The data were collected through caption by the government that related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Variation of language can be shown by the fact that the speakers can use different styles of speaking, called language styles (Juliana Dewi et al, 2020). Language style depends on many factors, such as education, social status, and the age and gender of the speaker (Pohan & Pohan, 2021). It is concluded that some factors influence the use of language style.…”
mentioning
confidence: 97%
“…Variation of language can be shown by the fact that the speakers can use different styles of speaking, called language styles (Juliana Dewi et al, 2020). Language style depends on many factors, such as education, social status, and the age and gender of the speaker (Pohan & Pohan, 2021). It is concluded that some factors influence the use of language style.…”
mentioning
confidence: 97%